hsa_circ_0007376 Promotes Gastric Cancer Proliferation and Malignant Metastasis by Enhancing the Stability of IGF2BP3 - Liang, LinHu; Han, Ting; Zhang, ZhengRong; Cheng, ZhengWu; Li, HaoRan (Turkish Journal of Gastroenterology, 2025)
Background/Aims: This study investigated the action of hsa_circ_0007376 in promoting the proliferation and metastasis of gastric cancer (GC). Materials and Methods: hsa_circ_0007376 was detected in GC tissues and cells by quantitative reverse transcription polymerase chain reaction. RNase R digestion, nucleoplasmic separation, and actinomycin D assays were conducted to detect the presence of hsa_circ_0007376 and its cyclic nature. The tumor-promoting effect of hsa_circ_0007376 in GC cells was verified by CCK-8, colony formation, wound healing, and Transwell assays. An interplay between hsa_circ_0007376 and insulin-like growth factor 2 mRNA binding protein 3 (IGF2BP3) was confirmed by FISH, RIP, and RNA pull-down experiments. The function of hsa_circ_0007376 on GC proliferation and metastasis was evaluated in vivo in a GC xenograft mouse model. Results: hsa_circ_0007376 was highly expressed in GC. hsa_circ_0007376 was associated with lymphatic metastasis, Tumor node metastasis (TNM) stage, and tumor size in GC. When hsa_circ_0007376 was knocked down, GC cells were prevented from proliferating, migrating, and invading, as well as being prevented from metastasizing. hsa_circ_0007376 was able to bind to IGF2BP3, thereby promoting GC. Conclusion: hsa_circ_0007376 may play a role in GC by interacting and enhancing the stability of the IGF2BP3 protein. Cite this article as: Liang L, Han T, Zhang Z, Cheng Z, Li H. hsa_circ_0007376 promotes gastric cancer proliferation and malignant metastasis by enhancing the stability of IGF2BP3. Turk J Gastroenterol. Published online May 20, 2025. doi 10.5152/tjg.2025.24491.